SAT0141 Optimal circulating adalimumab levels range associated with good clinical response in rheumatoid arthritis patients. (15th June 2017) - Jochems, A; Martinez-Feito, A; Plasencia, C; Hernández-Breijo, B; Mezcúa, A; Villalba, A; Monjo, I; Nozal, P; Balsa, A; Pascual-Salcedo, MD
Abstract : Background: TNF inhibitors have become an important part of healthcare worldwide for inflammatory diseases such as RA 1 . Many publications show that responding patients have higher Adalimumab (Ada) serum trough levels (ATL) than non-responders. These factors are influenced by age, weight, gender or pharmacokinetics, which in turn depend on immunogenicity. Concomitant use of immunomodulators such as methotrexate (MTX) reduces immunogenicity and enhances therapy benefits 1, 3 .Increasing drug dosage in patients with less response is the standard practice, while lowering dosage is advisable in patients achieving remission. Many recent publications 2 assess serum trough levels that reflect optimal response and which could be used as benchmark for guidance to implement the Therapeutic Drug Monitoring. Objectives: To establish an optimal Ada serum trough level (ATL) range in RA patients associated with good clinical response. Methods: A prospective observational study with 40 RA patients under Ada treatment recruited in the Rheumatology Unit of Universitary Hospital La Paz was conducted. Demographic data, ATL and clinical activity of patients treated with 40 mg/kg every other week from 4 months up to 12 years of treatment were collected. A total of 206 samples were analyzed [χ=5 (3–13) samples/patient]. Disease activity was assessed using the DAS28 index and clinical improvement with ΔDAS28. ATL were measured with a capture ELISA 3 [correlation with Promonitor (Derio, Vizcaya, Spain) k=1, r=0.91; and with Sanquin (Amsterdam, The Netherlands) k=1, r=0.86] and statistical analysis were performed with GraphPadPrism 5.0 software. Results: Demographic data of our cohort were: mean age (±SD) 56.75±16.06, with 82.5% of females and 45% of patients treated with concomitant MTX. Sixty-five and 72% of patients were RF and ACPA positive, respectively. ATL were similar in patients treated with concomitant MTX (χ=3.82±2.42 μg/ml) or Ada monotherapy (χ=3.54±2.43 μg/ml) p=0.81. Consistent with previous studies 1, 2, low-disease activity patients (DAS28≤3.2) presented higher Ada circulating levels than patients with high-disease activity [3.7 μg/ml (IQR 2.97–5.48) vs. 1.71 μg/ml (IQR 0.23–4.51), p=0.01]. The median of Ada levels excluding the values (n=6) that showed immunogenicity was 3.42 μg/ml (IQR 1.55–5.03) where 3.50 μg/ml represented the most frequent value (15% of patients). Lack of clinical improvement (ΔDAS<1.2) was linked to drug levels below percentile 25 (p=0.04) whilst Ada levels above percentile 75 did not ensure more clinical improvement (p=0.7) than the values around the median. Conclusions: ATL correlate with the disease activity and with the clinical improvement. The optimal range associated with good therapeutic response after the standard dose is 1.5–5 μg/ml . Higher circulating drug levels do not entail better response, which indicates they could be unnecessary. The knowledge of the optimal drug ranges can guide the Personalized Drug Therapy in order to maximise effectiveness and minimise costs. References: Pouw, M.F., et al. ARD, 2013. Chen, D., et al. ARD, 2014. Pascual- Salcedo, D. Rheumatology (Oxford), 2011. Disclosure of Interest: None declared